Role-Playing Strategy in Arabic Language Learning: Concepts, Theoretical Foundations, Implementation Model, and Implications - Rezkya Afril; Hanomi Hanomi; Rahmawati Rahmawati (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2026)
This article examines the role-playing strategy in Arabic language learning as a response to the persistent gap between learners' knowledge of vocabulary and grammar and their ability to use Arabic orally in meaningful interaction. The study aims to clarify the concept of role playing, synthesize its theoretical foundations, formulate a practical implementation model, and identify its pedagogical implications for developing maharah al-kalam. This research uses an integrative library research design. The data consist of conceptual statements, empirical findings, and methodological recommendations drawn from books, peer-reviewed journal articles, proceedings, and relevant research reports on role playing, communicative language teaching, active learning, social constructivism, experiential learning, Arabic speaking skills, and foreign language anxiety. The data were collected through documentation, selected by relevance, credibility, and recency, and analyzed through thematic synthesis involving data reduction, data display, comparison, interpretation, and conclusion drawing. The findings show that role playing is pedagogically relevant because it integrates linguistic forms, communicative functions, social interaction, affective support, and reflective feedback. Its implementation should be gradual: starting from guided dialogues, moving to semi-open scenarios, and ending with free or problem-based performances. Practically, this strategy requires clear objectives, sufficient language input, contextual scenarios, role distribution, rehearsal, performance, observation sheets, constructive feedback, and follow-up activities. Therefore, role playing should not be treated merely as an entertaining classroom activity, but as a structured communicative strategy for building speaking confidence, contextual vocabulary mastery, and meaningful Arabic language use.